Incidence, causes, and predictors of unsuccessful decannulation following prolonged weaning - Alessandro Ghiani; Konstantinos Tsitouras; Joanna Paderewska; Katrin Milger; Swenja Walcher; Mareike Weiffenbach; Claus Neurohr; Nikolaus Kneidinger (SAGE Publishing, 2022)
Background: Liberation from prolonged tracheostomy ventilation involves ventilator weaning and removal of the tracheal cannula (referred to as decannulation). This study evaluated the incidence, causes, and predictors of unsuccessful decannulation following prolonged weaning. Methods: Observational retrospective cohort study of 532 prolonged mechanically ventilated, tracheotomized patients treated at a specialized weaning center between June 2013 and January 2021. We summarized the causes for unsuccessful decannulations and used a binary logistic regression analysis to derive and validate associated predictors. Results: Failure to decannulate occurred in 216 patients (41%). The main causes were severe intensive care unit (ICU)-acquired dysphagia (64%), long-term ventilator dependence following weaning failure (41%), excessive respiratory secretions (12%), unconsciousness (4%), and airway obstruction (3%). Predictors of unsuccessful decannulation from any cause were age [odds ratio (OR) = 1.04 year −1 ; 95% confidence interval (CI), 1.02-1.06; p  < 0.01], body mass index [0.96 kg/m 2 (0.93-1.00); p  = 0.027], Acute Physiology and Chronic Health Evaluation II (APACHE-II) score [1.05 (1.00-1.10); p  = 0.036], pre-existing non-invasive home ventilation [3.57 (1.51-8.45); p  < 0.01], percutaneous tracheostomies [0.49 (0.30-0.80); p  < 0.01], neuromuscular diseases [4.28 (1.21-15.1); p  = 0.024], and total mechanical ventilation duration [1.02 day −1 (1.01-1.02); p  < 0.01]. Regression models examined in subsets of patients with severe dysphagia and long-term ventilator dependence as the main reason for failure revealed little overlapping among predictors, which even showed opposite effects on the outcome. The application of non-invasive ventilation as a weaning technique contributed to successful decannulation in 96 of 221 (43%) long-term ventilator-dependent patients following weaning failure. Conclusion: Failure to decannulate after prolonged weaning occurred in 41%, mainly resulting from persistent ICU-acquired dysphagia and long-term ventilator dependence following weaning failure, each associated with its own set of predictors.